A novel function of B‐cell translocation gene 1 (BTG1) in the regulation of hepatic insulin sensitivity in mice via c‐Jun. Issue 1 (22nd September 2015) - Xiao, Fei; Deng, Jiali; Yu, Junjie; Guo, Yajie; Chen, Shanghai; Guo, Feifan
ABSTRACT: Insulin resistance is one of the major factors contributing to metabolic diseases, but the underlying mechanisms are still poorly understood. As an important cofactor, B‐cell translocation gene 1 ( BTG1 ) is involved in many physiologic processes; however, the direct effect of BTG1 on insulin sensitivity has not been described. In our study, BTG1 overexpression or knockdown improved or impaired insulin signaling in vitro, respectively. In addition, adenovirus‐mediated BTG1 overexpression improved insulin sensitivity in wild‐type (WT) and insulin‐resistant leptin‐receptor mutated ( db/db ) mice. In addition, transgenic BTG1‐overexpressing mice were resistant to high‐carbohydrate diet‐induced insulin resistance. Adenovirus‐mediated BTG1 knockdown consistently impaired insulin sensitivity in WT and insulin‐sensitive leucine‐deprived mice. Moreover, hepatic BTG1 expression was increased by leucine deprivation via the mammalian target of rapamycin/ribosomal protein S6 kinase 1 pathway. Furthermore, c‐Jun expression was up‐regulated by BTG1, and adenovirus‐mediated c‐Jun knockdown blocked BTG1‐improved insulin signaling and insulin sensitivity in vitro and in vivo. Finally, BTG1 promoted c‐Jun expression via stimulating c‐Jun and retinoic acid receptor activities. Taken together, these results identify a novel function for BTG1 in the regulation of hepatic insulin sensitivity and provide important insights into the nutritional regulation of BTG1 expression.—Xiao, F., Deng, J., Yu, J., Guo, Y., Chen, S., Guo, F. A novel function of B‐cell translocation gene 1 ( BTG1 ) in the regulation of hepatic insulin sensitivity in mice via c‐Jun. FASEB J. 30, 348‐359 (2016). www.fasebj.org